Penyuluhan Pemanfaatan Kayu Sebagai Konstruksi Rumah Hunian Di Desa Sama Guna, Kecamatan Tanjung, Kabupaten Lombok Utara - Hidayati, Nurul; Adiansyah, Joni Safaat; Wahyuningsih, Titik; Hidayat, Ari Ramdhan; Ilmi, Muhammad Khalis; Yustissiani, Erni; Saputra, Adi; Fikri, M. Ali; Amandari, Ringka Ninis (Rengganis Jurnal Pengabdian Masyarakat, 2024)
Sama Guna Village is one of the villages in Tanjung District, North Lombok Regency which is the location of service by the Civil Engineering Study Program Service Team of Muhammadiyah Mataram University related to counseling on the use of wood as a residential house. The location of Sama Guna Village which is still beautiful and has a lot of green land makes this suburban a village that is considered appropriate and in accordance with the theme of the counseling to be carried out. The purpose of this service is to provide and share knowledge with the local community related to the introduction of good wood characteristics and can be used as a material for building residential houses for the community so that houses built from wood can become durable, strong, and long-lasting residential houses. The method used was presentation and discussion with the local community which took place on Saturday, June 15, 2024 starting at 10:00 - 12:30 WITA at the meeting room in Sama Guna Village. This activity ran smoothly and orderly, during the implementation of the activity the participants were very enthusiastic about participating in the activity, this was seen from the enthusiastic questions and answers that occurred with a total of 20 participants.